2013
DOI: 10.1155/2013/984594
|View full text |Cite
|
Sign up to set email alerts
|

Acute Dilatation, Ischemia, and Necrosis of Stomach without Perforation

Abstract: Acute gastric dilatation can have multiple etiologies which may lead to ischemia of the stomach. Without proper timely diagnosis and treatment, potentially fatal events such as gastric perforation, haemorrhage, and other serious complications can occur. Here we present a 36-year-old man who came to the casualty with pain abdomen and distension for 2 days. Clinically, abdomen was asymmetrically distended more in the left hypochondrium and epigastrium region. Straight X-ray abdomen showed opacified left hypochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 18 publications
0
25
1
7
Order By: Relevance
“…Total gastrectomy with oesophagojejunostomy, partial gastrectomy as well as wedge resection for acute gastric dilatation have been described. [4] Mishima T. et al, reported gastric necrosis and rupture in anterior part of stomach in a 12-yearold boy without any underlying disorders. [5] SungUi J et al, reported a case with rupture in the fundus in a 23-year-old-lady.…”
Section: Discussionmentioning
confidence: 98%
“…Total gastrectomy with oesophagojejunostomy, partial gastrectomy as well as wedge resection for acute gastric dilatation have been described. [4] Mishima T. et al, reported gastric necrosis and rupture in anterior part of stomach in a 12-yearold boy without any underlying disorders. [5] SungUi J et al, reported a case with rupture in the fundus in a 23-year-old-lady.…”
Section: Discussionmentioning
confidence: 98%
“…En effet, des auteurs rapportaient des tableaux cliniques non spĂ©cifiques : douleurs abdominales (65%), saignements gastro-intestinaux (47%), altĂ©ration de l'Ă©tat mental (23%), signes de choc, vomissements, syndrome de compression de la veine cave infĂ©rieure, avec une distension abdominale constante par la dilatation aiguĂ« de l'estomac (Sharma et al, 2017 ;Perpresse et al, 2013 ;TourĂ© et al, 2005). La nĂ©crose gastrique est suspectĂ©e devant la distension abdominale associĂ©e Ă  un tympanisme diffus et une crĂ©pitation gazeuse au niveau de l'hypogastre et du flanc gauche (Sahoo et al, 2013). Chez notre patient, la dĂ©couverte de la dilatation Ă©tait concomitante Ă  celle de la nĂ©crose gastrique, lors de l'exploration radiologique, sur un tableau clinique trompeur constituĂ© de vomissements avec mĂ©lĂ©na, dans un contexte apyrĂ©tique associĂ©e Ă  une pĂ©ritonite aiguĂ« gĂ©nĂ©ralisĂ©e dans un tableau d'altĂ©ration de l'Ă©tat gĂ©nĂ©ral.…”
Section: Discussionunclassified
“…Ainsi, l'imagerie est très contributive dans le diagnostic. En effet, l'abdomen sans prĂ©paration peut visualiser une volumineuse poche Ă  air gastrique pouvant s'Ă©tendre sur les hypochondres associĂ©e Ă  une pneumatose sous forme d'une clartĂ© linĂ©aire soulignant la lumière de l'estomac (Sahoo et al, 2013 ;TourĂ© et al, 2005 ;Gomez et al 2004). Comme dans notre cas, la tomodensitomĂ©trie abdominale a confirmĂ© le diagnostic devant un estomac distendu, sans prise de contraste de la paroi gastrique, mais accompagnĂ© d'images de pneumatoses et Ă©ventuellement d'une aĂ©roportie (TourĂ© et al, 2005 ;Gomez et al, 2004 ;Sharma et al, 2017).…”
Section: Discussionunclassified
See 2 more Smart Citations